Electrical Impedance-Based Electronic Tongues - Facure, Murilo H.M.; Braunger, Maria L. [UNESP]; Mercante, Luiza A.; Paterno, Leonardo G.; Riul, Antonio; Correa, Daniel S. (Elsevier, 2022)
Electronic tongues (e-tongues) are analytical tools using an array of sensors operating under distinct transduction mechanisms, combined with data treatment techniques to analyze complex liquid systems. Electrical impedance spectroscopy has been proven a useful detection method to e-tongues toward numerous analytes. In this book chapter, we address fundamental concepts of electrical impedance spectroscopy, interdigitated electrodes (IDEs), and their fabrication techniques. We also exemplify different (nano)materials and distinct deposition techniques for a functional coating of the IDEs. Alternative approaches for low-cost electrode fabrication and devices, including microfluidics and 3D printing, are also discussed. We also briefly survey data mining, machine learning, and visualization strategies in the big data context for e-tongues. Finally, applications of impedimetric e-tongues for the analyses of basic tastes, beverages, food, soil nutrients, pollutants, and other analytes of interest are illustrated and discussed.
Keywords: E-tongue; Electrode fabrication; Environmental applications; Food analyses; Impedance spectroscopy; Impedimetric electronic tongue; Interdigitated electrodes; Nanomaterials; Sensor array; Taste sensors